[64Cu]‐labelled trastuzumab: optimisation of labelling by DOTA and NODAGA conjugation and initial evaluation in mice. (24th April 2015) - Schjoeth‐Eskesen, Christina; Nielsen, Carsten Haagen; Heissel, Søren; Højrup, Peter; Hansen, Paul Robert; Gillings, Nic; Kjaer, Andreas
<x xml:space="preserve">Abstract</x> The human epidermal growth factor receptor‐2 (HER2) is overexpressed in 20–30% of all breast cancer cases, leading to increased cell proliferation, growth and migration. The monoclonal antibody, trastuzumab, binds to HER2 and is used for treatment of HER2‐positive breast cancer. Trastuzumab has previously been labelled with copper‐64 by conjugation of a 1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid (DOTA) chelator. The aim of this study was to optimise the 64Cu‐labelling of DOTA‐trastuzumab and as the first to produce and compare with its 1, 4, 7‐triazacyclononane, 1‐glutaric acid‐5, 7 acetic acid (NODAGA) analogue in a preliminary HER2 tumour mouse model. The chelators were conjugated to trastuzumab using the activated esters DOTA mono‐N‐hydroxysuccinimide (NHS) and NODAGA‐NHS. 64Cu‐labelling of DOTA‐trastuzumab was studied by varying the amount of DOTA‐trastuzumab used, reaction temperature and time. Full 64Cu incorporation could be achieved using a minimum of 10‐µg DOTA‐trastuzumab, but the fastest labelling was obtained after 15 min at room temperature using 25 µg of DOTA‐trastuzumab. In comparison, 80% incorporation was achieved for 64Cu‐labelling of NODAGA‐trastuzumab. Both [64Cu]DOTA‐trastuzumab and [64Cu]NODAGA‐trastuzumab were produced after purification with radiochemical purities of >97%. The tracers were injected into mice with HER2 expressing tumours. The mice were imaged by positron emission tomography and showed high tumour uptake of 3–9% ID/g for both tracers.